2017
DOI: 10.1089/wound.2016.0711
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNAs: New Players in Skin Wound Healing

Abstract: Significance: Wound healing is a basic physiological process that is utilized to keep the integrity of the skin. Impaired wound repair, such as chronic wounds and pathological scars, presents a major health and economic burden worldwide. To date, efficient targeted treatment for these wound disorders is still lacking, which is largely due to our limited understanding of the biological mechanisms underlying these diseases. Research driven around discovering new therapies for these complications is, therefore, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 133 publications
(187 reference statements)
1
48
0
Order By: Relevance
“…Accumulating evidence has reported the important roles of miRNAs and lncRNAs in wound healing, which add new insights to our understanding of wound complications 35 . Both lncRNAs and miRNAs are potential biomarkers for diagnosis and prognosis of wound healing treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has reported the important roles of miRNAs and lncRNAs in wound healing, which add new insights to our understanding of wound complications 35 . Both lncRNAs and miRNAs are potential biomarkers for diagnosis and prognosis of wound healing treatment.…”
Section: Discussionmentioning
confidence: 99%
“…TSIX and PRINS have been shown to be involved in the pathogenesis of systemic sclerosis and psoriasis, respectively (Sonkoly et al, 2005;Szell et al, 2016). However, the expression pattern and biologic functions of lncRNAs in skin wound healing remain largely unexplored (Herter and Xu Landen, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Wan et al have reported that lncRNAs play an important role in regulating the skin physiology function and diseases development [ 17 ]. Furthermore, they are also implicated in skin wound healing and hypertrophic scar formation [ 18 , 19 ]. As lncRNAs are expressed in a disease-, tissue- or developmental stage-specific manner, they are closely associated with malignant processes and so are attractive diagnostic and therapeutic targets [ 20 ].…”
Section: Discussionmentioning
confidence: 99%